2020
DOI: 10.1002/qua.26354
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate women empowering women in computational chemistry: Three perspectives

Abstract: The undergraduate computational chemistry research group headed by Mauricio Cafiero at Rhodes College has a history of including, promoting, and supporting women in this predominantly male field. Alums of this research group from 2004 to 2019 include nine M.Ds, two science researchers, two Ph.D.s, one secondary teacher, two pharmacists, a physical therapist, two nurses, six current medical school students, and five current science graduate students. They have produced 18 peerreviewed publications with female u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…found that applicants with male names are favored in a laboratory position hiring process rated by faculty participants . Joan Williams detailed the gender and racial biases on women in STEM from in-depth interviews with 60 female scientists. , In light of this pervasive issue, many address institutional solutions by calling for mentorship programs in universities and other educational institutes during women’s undergraduate and graduate careers. , Implementation of mentorship programs after college can continue to provide support to early career scientists and guidance for female leadership development . It is also proposed that organizations and companies should focus on diversity in the hiring stage and in promotion opportunities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that applicants with male names are favored in a laboratory position hiring process rated by faculty participants . Joan Williams detailed the gender and racial biases on women in STEM from in-depth interviews with 60 female scientists. , In light of this pervasive issue, many address institutional solutions by calling for mentorship programs in universities and other educational institutes during women’s undergraduate and graduate careers. , Implementation of mentorship programs after college can continue to provide support to early career scientists and guidance for female leadership development . It is also proposed that organizations and companies should focus on diversity in the hiring stage and in promotion opportunities .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In light of this pervasive issue, many address institutional solutions by calling for mentorship programs in universities and other educational institutes during women's undergraduate and graduate careers. 11,12 Implementation of mentorship programs after college can continue to provide support to early career scientists and guidance for female leadership development. 13 It is also proposed that organizations and companies should focus on diversity in the hiring stage and in promotion opportunities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Three recent graduates discuss how the above points affected them during their time in the research group and discuss their experience in the context of some literature on women in STEM. [10] The third perspective, by myself and Scott Feller of Wabash College, tackles the problem of how to stay active in research as your career progresses and your time is diminished and scattered because of other responsibilities. We draw on our experience as administrators to discuss strategies for how to maintain an active research program at a PUI as one's career progresses.…”
mentioning
confidence: 99%